Changes in Imja Tsho in the Mount Everest region of Nepal - Somos-Valenzuela, M. A.; McKinney, D. C.; Rounce, D. R.; Byers, A. C. (The Cryosphere, 2014)
Imja Tsho, located in the Sagarmatha (Everest) National Park of Nepal, is one of the most studied and rapidly growing lakes in the Himalayan range. Compared with previous studies, the results of our sonar bathymetric survey conducted in September of 2012 suggest that its maximum depth has increased from 90.5 to 116.3 ± 5.2 m since 2002, and that its estimated volume has grown from 35.8 ± 0.7 to 61.7 ± 3.7 million m3. Most of the expansion of the lake in recent years has taken place in the glacier terminus–lake interface on the eastern end of the lake, with the glacier receding at about 52 m yr−1 and the lake expanding in area by 0.04 km2 yr−1. A ground penetrating radar survey of the Imja–Lhotse Shar glacier just behind the glacier terminus shows that the ice is over 200 m thick in the center of the glacier. The volume of water that could be released from the lake in the event of a breach in the damming moraine on the western end of the lake has increased to 34.1 ± 1.08 million m3 from the 21 million m3 estimated in 2002.